Rebuilding the US Health Left - Matthew Anderson; Lanny Smith; Victor W. Sidel (Social Medicine Publication Group, 2024)
With this issue Social Medicine begins a series of invited papers on the topic: "Rebuilding the US Health Left." In this editorial we will outline our vision for this series. We undertake this project aware that our good friend and mentor, Dr. Walter Lear, one of the leading health activists of the 20th century, lies critically ill. Walter was the creator and custodian of the US Health Left Archives, a collection that is now with the University of Pennsylvania library. The collection reminds us of the important role left health care workers played in US history throughout the 20th century. They advocated for a national health program (Committee on the Costs of Medical Care, Physicians Forum, Medical Care Section/APHA, HealthPAC, Physicians for a National Health Program, National Physicians Alliance), provided international solidarity (American Soviet Medical Society, international brigades during the Spanish Civil War, Central American Solidarity Movement, Committee to Help Chilean Health Workers, Doctors for Global Health), traced the connections between disease and social class (Sigerist Circle, Spirit of 1848, APHA), fought for workers' health (Councils for Occupational Safety and Health; Occupational Health and Safety Section, APHA) participated in anti-war movements (Medical Committee for Human Rights, Physicians for Social Responsibility, International Physicians for the Prevention of Nuclear War), created new models of health care delivery (Health Cooperatives, Prepaid Health Maintenance Organizations, Community Health Centers, National Health Service Corps, Free Clinics), were central to the struggle for women's rights (Planned Parenthood, Physicians for Reproductive Choice and Health), supported the civil rights movement both in medicine and in the broader society (National Medical Association, Medical Committee for Human Rights), played key roles in the movement for gay rights (ACT-UP, Gay & Lesbian Medical Association, Lesbian, Gay, Bisexual, and Transgender Caucus of the APHA), challenged traditional models of medical education (Student Health Organizations, AMSA, Residency Program in Social Medicine), and worked in many, many other fields.